Dose-response relationship of weekly physical exercise on fitness of students - Carla Lourenço; Omar Ben Rakaa; João Vicente; Mustapha Bassiri; Said Lotfi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction. Childhood obesity and sedentary lifestyles highlight the critical need to understand the impact of physical exercise on fitness. This study investigates the dose-response relationship between weekly exercise volume and physical fitness components in adolescents using Portugal’s FITescola® assessment program.